Detection of Milk Spoilage Using Au D-Shaped Fiber Sensor based on Localized Surface Plasmon Resonance - Rosli, Farzana Nazurah; Awang, Noor Azura (Enhanced Knowledge in Sciences and Technology, 2026)
The effectiveness of gold nanoparticle coated D-shaped fiber sensor by utilizing localized surface plasmon resonance (LSPR) effect for detection of spoiled milk is studied. Milk is a highly perishable food product that is susceptible to spoilage due to microbial activity and improper storage conditions. Conventional methods for milk spoilage detection are often time-consuming, subjective, and require laboratory facilities. Therefore, this study investigates the feasibility of using an optical fiber–based sensor for the detection of milk spoilage through changes in optical response. An Au-coated D-shaped optical fiber sensor was developed based on the localized surface plasmon resonance (LSPR) effect to enhance sensitivity to refractive index variations in milk samples. Different types of milk, namely fresh milk, low-fat milk, full cream milk, and condensed milk, were prepared and allowed to undergo natural spoilage at room temperature over exposure periods of 0, 24, 48, and 72 hours. A thin gold (Au) layer was deposited using a sputter coater, and UV–Vis spectroscopy was employed to confirm the plasmonic characteristics of the coating. The sensor’s surface morphology was examined using field emission scanning electron microscopy (FESEM). Optical measurements were carried out using an Optical Spectrum Analyzer (OSA) and an Optical Power Meter (OPM) to monitor spectral changes and variations in transmitted optical power. The results demonstrated clear time-dependent changes in both spectral response and optical power for all milk samples, with more pronounced variations observed in full cream and condensed milk. These changes indicate sensitivity to compositional and refractive index variations associated with spoilage.